Alteration of Surface EMG amplitude levels of five major trunk muscles by defined electrode location displacement. Issue 2 (April 2015) - Huebner, Agnes; Faenger, Bernd; Schenk, Philipp; Scholle, Hans-Christoph; Anders, Christoph
Abstract: Exact electrode positioning is vital for obtaining reliable results in Surface EMG. This study aimed at systematically assessing the influence of defined electrode shifts on measured Surface EMG amplitudes of trunk muscles in a group of 15 middle aged healthy male subjects. The following leftsided muscles were investigated: rectus abdominis muscle, internal and external oblique abdominal muscles, lumbar multifidus muscle, and longissimus muscle. In addition to the recommended electrode positions, extra electrodes were placed parallel to these and along muscle fiber direction. Measurements were performed under isometric conditions in upright body position. Gradually changing, but defined loads were applied considering subject's upper body weight. For the abdominal muscles amplitude differences varied considerably depending on load level, magnitude, and direction. For both back muscles amplitudes dropped consistently but rather little for parallel electrode displacements. However, for the longissimus muscle a caudal electrode shift resulted in an amplitude increase of similar extent and independent from load level. Influence of electrode position variations can be proven for all trunk muscles but are more evident in abdominal than back muscles. Those muscle-specific effects confirm the necessity for an exact definition of electrode positioning to allow comparisons between individual subjects, groups of subjects, and studies.